English teacher’s strategies in providing written feedback and students’ responses to the feedback at SMPN 12 Padang - Ginting, Dyah Ayu Lestari; Fatimah, Sitti (Journal of English Language Teaching, 2025)
This study aims to analyze teacher’s strategies in providing direct and indirect written feedback through semi structured interview, and to analyze students’ responses in their cognitive, affective, and behavioral responses through questionnaire and focus group discussion. The research was conducted at SMP Negeri 12 Padang with 65 ninth-grade students who came from class IX-2 and IX-4, and 1 English teacher. Descriptive quantitative research approach was employed because the main goal was to describe the existing phenomenon of students’ responses statistically through frequencies and percentages. From the results, it showed that most of students preferred direct feedback with the percentage 88.8% rather than indirect feedback with the percentage 70.75%. The results indicated that the teacher provided both of the feedback, but direct feedback was more frequently and consistently used. Most students preferred direct feedback as it is clearly showed their mistakes, enable immediate correction, and helped them understand. However, some students appreciated indirect feedback because they thought it encouraged them to think critically, searched for the answers independently, and less dependent on the teacher. In the affective responses, 80.7% students said that written feedback made them feel confident, 87.6% said that they were motivated to write better. In behavioral responses, 64.6% students tried to ask teacher if there was something that they did not know, and 75.3% students tried to correct the mistakes that the teacher had marked. The study concludes that combining direct and indirect written feedback can enhance students’ writing skills and increase their motivation in writing.